2021
DOI: 10.1371/journal.pone.0247599
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on cement-improved phyllite based on the vertical vibration compaction method

Abstract: The vertical vibration compaction method (VVCM), heavy compaction method and static pressure method were used to form phyllite specimens with different degrees of weathering. The influence of cement content, compactness, and compaction method on the mechanical properties of phyllite was studied. The mechanical properties of phyllite was evaluated in terms of unconfined compressive strength (Rc) and modulus of resilience (Ec). Further, test roads were paved along an expressway in China to demonstrate the feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Fig 1 illustrates the structure of the VVTE. The working parameters of the VVTE included a vibration frequency of 35 Hz, a nominal amplitude of 1.2 mm, and upper-and lower-system weights of 120 and 180 kg, respectively [17][18][19][20][21].…”
Section: Specimen Preparation Methodsmentioning
confidence: 99%
“…Fig 1 illustrates the structure of the VVTE. The working parameters of the VVTE included a vibration frequency of 35 Hz, a nominal amplitude of 1.2 mm, and upper-and lower-system weights of 120 and 180 kg, respectively [17][18][19][20][21].…”
Section: Specimen Preparation Methodsmentioning
confidence: 99%
“…The preliminary research and related studies have compared the VVCM with the heavy compaction method (HCM) and static compaction method (SCM), fully demonstrating that the VVCM moulding method has better field correlation than the HCM and SCM. Because of different compaction mechanisms, the mechanical strength of the VVCM-moulded specimens is also higher than those moulded by the HCM and SCM [ 30 , 31 , 32 ].…”
Section: Raw Materials and Test Plansmentioning
confidence: 99%
“…The CBR of phyllite with 6% cement content is about twice that with 3% cement content, and when the cement content is greater than 3% it can meet the requirements of subgrade specifications. Jiang et al [15] found that for every 1% increase in cement content, the unconfined compressive strength of phyllite increased by at least 15%, and the modulus of resilience increased by at least 17%. When the cement content was 2%, the modulus of resilience of the subgrade was 64 MPa, which could meet the requirement of the "Class I Highway subgrade".…”
Section: Introductionmentioning
confidence: 99%